2016
DOI: 10.1002/2016ea000168
|View full text |Cite
|
Sign up to set email alerts
|

A method for automated snow avalanche debris detection through use of synthetic aperture radar (SAR) imaging

Abstract: Avalanches are a natural hazard that occur in mountainous regions of Troms County in northern Norway during winter and can cause loss of human life and damage to infrastructure. Knowledge of when and where they occur especially in remote, high mountain areas is often lacking due to difficult access. However, complete, spatiotemporal avalanche activity data sets are important for accurate avalanche forecasting, as well as for deeper understanding of the link between avalanche occurrences and the triggering snow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…7). Our results show that avalanches were also detected on slopes steeper than 35 • , thus highlighting the limits of detection methods using arbitrary slope thresholds (Bühler et al, 2009;Vickers et al, 2016). Out of 193, 139 of the highest-lying avalanches (> 2800 m a.s.l.)…”
Section: Topographic Factors Favourable For Snow Avalanchesmentioning
confidence: 63%
See 2 more Smart Citations
“…7). Our results show that avalanches were also detected on slopes steeper than 35 • , thus highlighting the limits of detection methods using arbitrary slope thresholds (Bühler et al, 2009;Vickers et al, 2016). Out of 193, 139 of the highest-lying avalanches (> 2800 m a.s.l.)…”
Section: Topographic Factors Favourable For Snow Avalanchesmentioning
confidence: 63%
“…Previous studies have demonstrated that a combination of aerial images and digital elevation models (Bühler et al, 2009), or aerial (Lato et al, 2012 and satellite (Larsen et al, 2013), or SAR images (Vickers et al, 2016) favours the automatic detection of snow-avalanche deposits; however, identifying release zones and tracks remains challenging. We propose an OBIA algorithm that tracks release zones, tracks, and run-out zones in NIR images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mapped avalanches described in this paper are a unique training and validation dataset as it contains a large number of individual avalanches in differing topography and illumination conditions 5 over a very large region. The same applies for the validation of existing mapping product from radar satellite data (Eckerstorfer et al, 2017;Vickers et al, 2016;Wesselink et al, 2017).…”
Section: Potential Improvements and Follow Up Analysismentioning
confidence: 96%
“…Radar satellites have the advantage of acquiring data despite clouds and without daylight. Therefore, radar data has also been applied to generate avalanche maps (Eckerstorfer and Malnes, 2015;Vickers et al, 2016;Eckerstorfer et al, 40 2017;Wesselink et al, 2017). Due to the coarser spatial resolution (3 -30 m) and limitations by the observation geometries (radar shadow and layover), considerable parts of mountain regions cannot be covered.…”
Section: Introduction 30mentioning
confidence: 99%